Effect of Different Levels of Energy Diet Restriction on Energy Balance, Leptin and CL Development, Vascularization, and Function in South American Camelids - Norambuena, Cecilia; Hernandez, Francisca; Alfaro, Jorge; Silva, Gonzalo; Topp, Shirley; Ratto, Marcelo (Frontiers in Veterinary Science, 2020)
The objective was to determine the effect of energy diet restriction on energy balance, systemic leptin, and CL vascularization, development and function in South American camelids. In experiment 1, adult llamas were randomly assigned to receive a diet of 70% of their maintenance energy requirements (MER) (Restricted group, n = 7) or fed with ad libitum (Control group, n = 7) during 28 d. Body live weight (BLW), body condition score (BCS) were recorded and blood samples were collected, every 2 weeks, to measure plasma leptin concentrations and energy metabolites were quantify. In experiment 2, adults alpacas were randomly assigned to receive a diet of 40% MER for 21 d (Restricted group, n = 7) or fed with ad libitum (Control group, n = 7). Then, ovulation was induced with gonadorelin acetate (Day = 0), and trans-rectal ultrasonography (7.5 MHZ) was performed using B and Doppler mode to record the diameter of the pre-ovulatory follicle, ovulation, CL diameter and vascularization from Day 0 -13. Blood samples were collected every 48 h from Day 1-13 to quantify plasma leptin and progesterone concentrations. In experiment 1, energy diet restriction of 70% MER did not affect plasma leptin concentration and metabolic parameters of the Restricted group. In experiment 2, the Restricted group had a lower BCS (P <0.001), a smaller diameter of the CL on days 5 and 7 (P <0.05) and a smaller maximum diameter of the CL (10.2 ± 0.6 mm) than the Control group (12.1 ± 0.6 mm; P = 0.04). Low energy restriction of 70% MER for 28 d did not affect the energy balance of llamas (Experiment 1). Moderate energy restriction of 40% MER for 21 d negatively affected energy balance (BCS), and CL development but not its vascularization, leptin and progesterone concentrations. These species must be submitted to longer periods or a higher levels of energy restriction to impair ovarian function.